Odpowiedź :
[tex]a=\frac{3\frac{1}{8}}{2\frac{3}{8}-1,75}=\frac{3\frac{1}{8}}{2\frac{3}{8}-1\frac{75}{100}}=\frac{3\frac{1}{8}}{2\frac{3}{8}-1\frac{3}{4}}=\frac{3\frac{1}{8}}{2\frac{3}{8}-1\frac{6}{8}}=\frac{3\frac{1}{8}}{1\frac{11}{8}-1\frac{6}{8}}= \frac{ \frac{25}{8}}{ \frac{5}{8} }=\\\\\\=\frac{25}{8}:\frac{5}{8}=\frac{\not{25}^5}{\not{8}^1}*\frac{\not{8}^1}{\not{5}^1}= 5\\\\\\b=8\frac{4}{7}*(0,75- \frac{2}{5})=\frac{60}{7}*( \frac{75}{100}- \frac{2}{5})=\frac{60}{7}*( \frac{3}{4}- \frac{2}{5})=\frac{60}{7}*( \frac{15}{20}- \frac{8}{20})=\\\\\\=\frac{\not{60}^3}{\not{7}^1}*\frac{\not{7}^1}{\not{20}^1}=3\\\\\\a=5,\ \ \ b=3[/tex]
[tex]Liczba\ a\ jest\ o\ 2\ mniejsza\ od\ liczby\ b.\\\\a-b=5-3=-2\\\\FALSZ\\\\\\Liczba\ b\ stanowi\ 0,6\ liczby\ a.\\\\b=5*0,6=3\\\\PRAWDA[/tex]